(3VeGfGJ GdeMche Ydjg NdGd aJQI GdJfajP GdYbGHj (B/ s - (3GdSjO CMeO eMeO YdGes; (3eMehO eMeO cHjT s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3JfGhd deMI JGQjNjI dJWhQ VeGfGJ GdeMche Ydjg NdGd aJQI GdJfajP GdYbGHj HOA ef GdMjGI GdHOGFjI GdChdj hUhdB Edj GdYUQ GdMOjK Ke JfGhd GdVeGfGJ GdeJYdbI HGdbGFejf Ydj GdJfajP GdYbGHj(B: (3hjTed GdEOGQI GdYbGHjI h GdbVGA h OhQgeG ai GdJajP GdYbGHi h cjajI GdWYf Ydi bQGQGJ GdEOGQI GdYbGHjI h bVGA GdJfajP CeGe GdbVGA GdYGOi h GdEOGQi GdYbGHjI h bVGA GdJfajP CeGe GdbVGA GdYGOj h GdEOGQj Ke JfGhd GdVeGfGJ GdeJYdbI HELQGAGJ GdJfajP GdYbGHj(B: (3h jTed VeGfGJ TQYjI GdJfajP GdYbGHj aj GdJTQjY GdhVYj h GdESdGejs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2012s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B543-569s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdVeGfGJ s; (3GdeMche Ydjg s; (3aJQI GdJfajP GdYbGHj s; (3GdGOGQI GdYbGHjIs; (3GdLRGAGJ GdJCOjHjIs; (3GdSLjfs; (3GdGaQGLs; (3OhQ GdbVGA ai GdJajP GdYbGHjs; (3GdbGfhf GdHQJZGdjs; (3GdbGfhf GdGjWGdjs; (3VeGfGJ GdeYGedI ai GdeDSSGJ GdYbGHjIs; (3GeGcf GdJfajP GdYbGHjs; (3GTcGdGJ GdJfajPs; (3GdbGfhf GdaQfSjs; (3GdWYf Ydj bQGQJ GdJfajPs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs